Sequencing of 28SrRNA Gene for Identification of Trichoderma longibrachiatum 28CP/7444 Species in Soil Sample - Shahid, Mohammad; Singh, Anuradha; Srivastava, Mukesh; Rastogi, Smita; Pathak, Neelam (International Journal of Biotechnology for Wellness Industries, 2013)
Most of the Trichoderma species are morphologically very similar and were considered for many years as a single species. Since new species were discovered, a consolidated taxonomical scheme was needed and proposed and defined nine morphological species aggregates. DNA methods brought additional valuable criteria to the taxonomy of Trichoderma which are being used today for studies that include identification and phylogenetic classification. Most isolates of the genus Trichoderma that were found to act as mycoparasites of many economically important aerial and soil-borne plant pathogens. Trichoderma has attained importance for substitute of chemical pesticides and hence an attempt was intended to corroborate the positive relatedness of molecular and morphological characters. A fungal strain of Trichoderma longibrachiatum 28CP/7444 was isolated from a soil sample collected from Barabanki district of Uttar Pradesh, India. The universal primers were used for amplification of the 28S rRNA gene fragment and strain characterized by using 28S rRNA gene sequence with the help of ITS marker. It is proposed that the identified strain Trichoderma longibrachiatum 28CP be assigned as the type strain of a species of the genus Trichoderma based on phylogenetic tree analysis together with the 28S rRNA gene sequence search in Ribosomal Database Project, small subunit rRNA and large subunit rRNA databases. The sequence was deposited in GenBank with the accession number JX978541. Thus an integrated approach of morphological and molecular markers can be employed to identify a superior strain of Trichoderma for its commercial exploitation.